Program Kemitraan Sekolah sebagai Strategi Peningkatan Animo Mahasiswa Baru FKIP Universitas Mulawarman di Bulungan Kalimantan Utara - Didik Cahyono; Agung Rahmadani; Rizal Izmi Kusumawijaya (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Universities in border areas face challenges in recruiting prospective new students due to limited access to higher education information and low levels of advanced literacy studies among high school students. Bulungan Regency, as a border area in North Kalimantan, demonstrates this condition, which has an impact on the low number of high school graduates who continue their studies at Mulawarman University, especially the Faculty of Teacher Training and Education (FKIP). This community service activity aims to build a partnership strategy between FKIP Mulawarman University and Tanjung Palas State Senior High School and Tanjung Selor State Senior High School as an effort to improve students' understanding of higher education and increase enthusiasm for new student admissions. The implementation method uses a participatory university-school partnership approach through campus socialization activities, educational career workshops, student inspiration classes, virtual campus tours, guidance counselor training, and new student registration assistance. The evaluation program was conducted using pre-test and post-test questionnaires, interviews, and documentation of student registration data. The results of the activity showed a significant increase in students' understanding of FKIP Mulawarman University, from 42% to 85% at Tanjung Palas State Senior High School and from 45% to 88% at Tanjung Selor State Senior High School. The satisfaction rate of partner schools with the program is above 90%, and there has been an increase in student interest in continuing their studies at university. The program also strengthens the role of guidance counselors as information agents for higher education and fosters a sustainable collaborative network between universities and schools. It can be concluded that the School Partnership Program is effective as a strategy to increase new student enrollment at the Faculty of Teacher Training and Education at Mulawarman University and serves as a model for university service in expanding access to higher education in border areas. This program is recommended for continuation and implementation at other schools in North Kalimantan.